Pengaruh Budaya Organisasi, Kualitas Kerja, Loyalitas Kerja Terhadap Kinerja Karyawan CV. Wibisono Kreatif - Nila Mashluha Sukma Nahdliyana; Sofyan Lazuardi; Noneng R. Suktmadiredja (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study investigates the impact of organizational culture, work quality, and work loyalty on employee performance at CV. Wibisono Kreatif Media. Utilizing a quantitative approach, it sampled 38 employees through saturated sampling and collected data via questionnaires. Analysis was conducted using multiple linear regression with SPSS software. The findings reveal that organizational culture (X1), work quality (X2), and work loyalty (X3) collectively have a significant effect on employee performance (Y), evidenced by an F count of 66.066 and a significance value of 0.001. Specifically, organizational culture significantly influences performance (t-count 2.692, sig 0.011), as does work quality (t-count 3.078, sig 0.004). However, work loyalty does not significantly affect performance (t-count 1.608, sig 0.117). The determination test indicates that 85.4% of employee performance can be explained by the independent variables, leaving 37.9% attributed to other factors. Overall, the study highlights the importance of organizational culture and work quality in enhancing employee performance, while work loyalty appears less impactful.